Drained deformation and failure due to cyclic pore pressures in soft natural clay at low stresses - Eigenbrod, K. D.; Burak, J.-P.; Graham, J. (Canadian Geotechnical Journal, 1987)
Slow, recurring downslope movements in northern climates are frequently referred to as "creep movements," and are usually related to outwards freezing followed by vertical thawing movements. An alternative mechanism is examined in the reported test data.Undisturbed block samples of proglacial clay from a slope near yellowknife, N.W.T., have been tested by cyclically varying the pore-water pressure in triaxial specimens by an amount Δu, and measuring the resulting strains per cycle. The specimens were initially anisotropically consolidated with normal and shear stresses corresponding to those in the moving mantle. Drainage was permitted throughout the testing. This procedure represents changes that can occur in a natural slope from (a) seasonal groundwater level changes and (b) elevated pore-water pressures that accompany thawing. After 60–100 cycles, the pore-water pressure was systematically increased to the value Δu f at which the samples failed. This occurred on a steep, low-stress envelope, approximately c′ = 4 KPa, [Formula: see text]. The envelope is probably controlled by the nuggety macrostructure of the clay and appears to be slightly to the left of the [Formula: see text] locus.The strains per cycle were approximately linear in the range 30–100 cycles. As a first approximation they have been modelled as varying linearly with the ratio Δu/Δu f almost up to failure at Δu/Δu f = 1.0. Key words: downslope creep, solifluction, slope stability, clay, pore-water pressure, cyclic loading, low-stress failure.